2022
DOI: 10.21203/rs.3.rs-1546340/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphisms of the melatonin receptor 1A (MTNR1A) gene affect sexual performance of Rasa Aragonesa rams without changing their social dominance

Abstract: The aim of this study was to investigate whether a specific genotype of the MTNR1A gene influences social dominance and reproductive performance in rams. Thirty-one rams were genotyped for Rsal and Mnll polymorphism of the gene: CC (n = 19), CT (n = 5), and TT (n = 7), and GG (n = 20), GA (n = 6), or AA (n = 5), respectively. Social behavior was recorded by direct observations, and rams were tested in individual serving-capacity tests. The genotypes did not differ in the numbers of aggressions that they perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…At the pre-pubertal stage, a ram's social rank can affect how well it reproduces in adulthood, although testosterone serum levels and semen output are not correlated with social rank (Ungerfeld and Lacuesta 2010). Our earlier research showed that the social hierarchy in the ram flock was not related to the increase in the rams' sexual performance in the spring that carried particular genotypes of the MTNR1A gene (Abecia et al 2022). Rams that carried the TT genotype at position g.17355458 C>T, and the GG genotype at position g.17355452G>A performed sexually better in the spring, but their social status was not significantly different from that of the rams that carried the other genotypes.…”
Section: Discussionmentioning
confidence: 85%
“…At the pre-pubertal stage, a ram's social rank can affect how well it reproduces in adulthood, although testosterone serum levels and semen output are not correlated with social rank (Ungerfeld and Lacuesta 2010). Our earlier research showed that the social hierarchy in the ram flock was not related to the increase in the rams' sexual performance in the spring that carried particular genotypes of the MTNR1A gene (Abecia et al 2022). Rams that carried the TT genotype at position g.17355458 C>T, and the GG genotype at position g.17355452G>A performed sexually better in the spring, but their social status was not significantly different from that of the rams that carried the other genotypes.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, the possible role of specific genotypes of the melatonin receptor 1A (i.e., MTNR1A ) gene in social dominance and reproductive success was tested in rams. Although some males carrying certain genotypes of the MTNR1A gene displayed the best sexual performance, such superiority was exerted in a non-social hierarchized fashion [ 45 ].…”
Section: Discussionmentioning
confidence: 99%